Functional study of two flexible regions of the hepatitis E virus ORF1 replicase - Léa Mézière; Sonia Fieulaine; Claire Montpellier; Martin Ferrié; Thibault Tubiana; Gabriel Vanegas Arias; Stéphane Bressanelli; Laurence Cocquerel; Cécile-Marie Aliouat-Denis (PLoS ONE, 2026)
Hepatitis E virus (HEV), like other positive-sense RNA viruses, encodes a multidomain protein essential for replication, termed ORF1. However, the number, organization, and functions of its domains remain debated. Using AlphaFold2-based structural modeling, we investigated two structurally disordered regions with potential regulatory functions: (i) a 16-residue linker between the Helicase (Hel) and RNA-dependent RNA polymerase (RdRp) domains, proposed as a cleavage site and/or a flexible hinge, and (ii) the RdRp C-terminal tail, suggested to modulate polymerase activity through conformational plasticity. We performed mutagenesis of the Hel/RdRp linker and analyzed the impact of mutations on ORF1 maturation, subcellular localization, and replication efficiency. Using an extensive antibody panel combined with precise protein sizing, we found that ORF1 is predominantly expressed as a full-length protein with an apparent molecular weight of ~235 kDa by SDS-PAGE, together with several low-abundance truncated products, including the previously described HEV-derived SMAD activator (HDSA) fragment. These results suggest that ORF1 likely undergoes post-translational modifications and partial maturation by cellular proteases and/or spontaneous truncations in exposed regions. Importantly, Hel/RdRp linker mutations did not alter the ORF1 expression profile or subcellular localization, arguing against cleavage within this region. However, substitutions of conserved residues in the linker strongly impaired HEV replication, highlighting the functional importance of this disordered segment for viral genome replication. Boltz-1 structural modeling suggests a direct involvement of the Hel-RdRp linker in positioning the two enzymes, particularly for synthesis of the subgenomic RNA. Similarly, deletions or substitutions within the last 20 C-terminal RdRp residues abolished or severely impaired HEV replication. This demonstrates that the conformational flexibility of the RdRp C-terminal segment is likely critical for ORF1 function, e.g., for polymerase activity. In conclusion, although ORF1 likely undergoes tightly regulated processing, cleavage is unlikely to occur within the Hel/RdRp linker. Nevertheless, this segment and the conformational dynamics of the RdRp C-terminus emerge as key regulatory elements required for efficient HEV replication, pointing to novel mechanistic layers of control in the HEV replication process.